Centering Indigenous knowledge in suicide prevention: a critical scoping review - Erynne Sjoblom; Winta Ghidei; Marya Leslie; Ashton James; Reagan Bartel; Sandra Campbell; Stephanie Montesanti (BMC, 2022)
Abstract Background Indigenous peoples of Canada, United States, Australia, and New Zealand experience disproportionately high rates of suicide as a result of the collective and shared trauma experienced with colonization and ongoing marginalization. Dominant, Western approaches to suicide prevention-typically involving individual-level efforts for behavioural change via mental health professional intervention-by themselves have largely failed at addressing suicide in Indigenous populations, possibly due to cultural misalignment with Indigenous paradigms. Consequently, many Indigenous communities, organizations and governments have been undertaking more cultural and community-based approaches to suicide prevention. To provide a foundation for future research and inform prevention efforts in this context, this critical scoping review summarizes how Indigenous approaches have been integrated in suicide prevention initiatives targeting Indigenous populations. Methods A systematic search guided by a community-based participatory research (CBPR) approach was conducted in twelve electronic bibliographic databases for academic literature and six databases for grey literature to identify relevant articles. the reference lists of articles that were selected via the search strategy were hand-searched in order to include any further articles that may have been missed. Articles were screened and assessed for eligibility. From eligible articles, data including authors, year of publication, type of publication, objectives of the study, country, target population, type of suicide prevention strategy, description of suicide prevention strategy, and main outcomes of the study were extracted. A thematic analysis approach guided by Métis knowledge and practices was also applied to synthesize and summarize the findings. Results Fifty-six academic articles and 16 articles from the grey literature were examined. Four overarching and intersecting thematic areas emerged out of analysis of the academic and grey literature: (1) engaging culture and strengthening connectedness; (2) integrating Indigenous knowledge; (3) Indigenous self-determination; and (4) employing decolonial approaches. Conclusions Findings demonstrate how centering Indigenous knowledge and approaches within suicide prevention positively contribute to suicide-related outcomes. Initiatives built upon comprehensive community engagement processes and which incorporate Indigenous culture, knowledge, and decolonizing methods have been shown to have substantial impact on suicide-related outcomes at the individual- and community-level. Indigenous approaches to suicide prevention are diverse, drawing on local culture, knowledge, need and priorities.